Editorial: Biodiversity, multiculturalism and knowledge management - El Director (2024)
In Peru, during the year 2022, total exports reached USD 63,193 million. Of this sum, only approximately 3% (USD 1,200 million) corresponded to exports of services and technological products, an insignificant figure compared to traditional products such as minerals and agricultural products. These data, provided by entities such as PROMPERÚ and the Central Reserve Bank of Peru (BCRP), highlight the predominance of the primary export model and largely explain the disparities in our sustainable development. This has a negative impact on economic diversification, the competitiveness of the productive fabric and the environment.